Imaniyatul PENGENALAN MINAT DAN BAKAT ANAK KELUARGA PENGEMIS DI KECAMATAN PRAGAAN SUMENEP: Latar Belakang Masalah - Fithriyah, Imaniyatul (Universitas Negeri Surabaya, 2024)
he begging culture in Indonesia is based on various factors, one of which is family factors which have been working as beggars for generations. This will also have an impact on their offspring who tend to be accustomed to becoming beggars. This phenomenon also occurs in Sumenep Regency, specifically in Pragaan District, especially in Pragaan Daya Village. This service is carried out using the Asset Based Community-Driven Development (ABCD) method. Determining the ABCD method is considered relevant because a) it seeks to improve negative habits that have been going on for generations into habits of positive behavior by providing enlightenment on the importance of recognizing and understanding one's talents and interests, b) an effort to provide understanding about optimizing one's potential for career planning. The results of the service show that children from beggar families need assistance to recognize and understand their potential in terms of interests, talents and abilities before planning further education and work that will be carried out and decided by each child from beggar families in Pragaan Daya village, Sumenep. . The results of this service recommend that for the implementation of further service, it should be focused on sustainable mentoring efforts to further explore the personal potential and career decision making of each child from beggar families in Pragaan Daya village.